Where do babies come from? - Royston, Angela, 1945-.; Donaera, Patrizia; Gorton, Steve; Price, Susanna (New York : DK Pub., 1996)
An introduction for young children on how life begins.
Keywords: Sex instruction for children; Sex instruction for children -- Juvenile literature; Reproduction -- Juvenile literature; Reproduction; Babies